MANAJEMEN PENGEMBANGAN KURIKULUM PENDIDIKAN ANAK USIA DINI DI KBIT ALFURQON SUMBANG BANYUMAS DAN PLAY GROUP GENUS JATIWINANGUN PURWOKERTO - Maspupah, Ulpah (IAIN Tulungagung, 2018)
Based on the analysis of the data, the researcher acquired findings that: (1) Step management of curriculum development from KBIT Alfurqon is less detailed, just the outline, its dfferent from Play Group Genus that more detailed and well plan; (2) Step curriculum organizing in KBIT Alfurqon and Play Group Genus are well organized, including organizing on plan, implementation and evalution, the difference are appoinment of home teachers and tutor centers, curriculum organizing in KBIT Alfurqon include intern curriculum , curriculum plus, habituation, extra curriculum, while curriculum organizing in Play Group Genus include intern curriculum and extra curriculum; (3) Step of intern curriculum implementation in KBIT Alfurqon or Play Group Genus are using Beyond Center and Circle Time (BCCT), and the similarity from KBIT Alfurqon and Play Group Genus on extra curriculum implementation covers cooking and Outing class; (4) step of curriculum evaluation has done to curriculum reviewers and evaluation process to educators and learners, and for assesment tools that used by KBIT Alfurqon and Play Group Genus are portpolio, work method, assignment and masterpiece, the different assesment tool that used by Play Group Genus beside four things above are daily observation, cheklist, recording special events or anekdot, interview or conversation.